Overview of Financial Planning in India: Exploring the Process of Financial Planning in India (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Financial planning is industries that emerge from the desire of households to receive financial advice from a single source. According to the Financial Planning Association, a main industry organization representing financial planners, financial planning is a process that involves taking stock of all existing resources of individuals, developing a plan to utilize them, and systematically implementing the plan in order to achieve short- and long-term goals of individuals.